2020
DOI: 10.1021/acsami.0c17633
|View full text |Cite
|
Sign up to set email alerts
|

Photothermally Active Cryogel Devices for Effective Release of Antimicrobial Peptides: On-Demand Treatment of Infections

Abstract: There has been significant interest in the use of peptides as antimicrobial agents, and peptide containing hydrogels have been proposed as biological scaffolds for various applications. Limited stability and rapid clearance of small molecular weight peptides pose challenges to their widespread implementation. As a common approach, antibacterial peptides are physically loaded into hydrogel scaffolds, which leads to continuous release through the passive mode with spatial control but provides limited control ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Hydrogels can be incorporated with drugs to improve antibacterial properties via π−π stacking, reversible covalent cross-links [ 105 ], and direct encapsulation [ 106 ]. A photothermal trigger or pH trigger can be chosen to control drug release [ 107 ].…”
Section: Potential Mechanisms Of Photothermal Hydrogels For Wound Healing and Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogels can be incorporated with drugs to improve antibacterial properties via π−π stacking, reversible covalent cross-links [ 105 ], and direct encapsulation [ 106 ]. A photothermal trigger or pH trigger can be chosen to control drug release [ 107 ].…”
Section: Potential Mechanisms Of Photothermal Hydrogels For Wound Healing and Tissue Engineeringmentioning
confidence: 99%
“…As shown in Figure 2, after the bacteria were incubated with the hydrogel, the cell membranes were damaged to varying degrees [104]. Hydrogels can be incorporated with drugs to improve antibacterial properties via π−π stacking, reversible covalent cross-links [105], and direct encapsulation [106]. A photothermal trigger or pH trigger can be chosen to control drug release [107].…”
Section: Antibacterial Effectsmentioning
confidence: 99%
“…Therapeutic agents may not necessarily be represented solely by drug molecules. Recent examples of other types of therapeutic cargos used for delivery by cryogels include fertilizers for agrochemical applications [ 103 ], peptides [ 104 ], proteins [ 37 ], and growth factors [ 81 , 105 106 ]. For example, Lee et al reported the use of a double cryogel structure for the delivery of growth factor for enhanced bone regeneration [ 105 ].…”
Section: Reviewmentioning
confidence: 99%
“…Animal experiments have shown that this antibiotic-free cryogel is effective in killing microbes in a wound and accelerating wound healing, and is therefore a promising wound dressing material for clinical use. Photo-thermally active cryogels have been prepared for the release of antimicrobial peptides [ 154 ]. The peptides were covalently conjugated onto furan-based cryogel scaffolds by Diels-Alder cycloaddition and were enabled to release “on-demand” at NIR exposure to kill bacteria.…”
Section: Biodegradable Cryogelsmentioning
confidence: 99%